Outlook for Remittance Flows 2012-14 : Remittance Flows to Developing Countries Exceed $350 Billion in 2011 - Mohapatra, Sanket; Ratha, Dilip; Silwal, Ani (World Bank, Washington, DC, 2013)
Officially recorded remittance flows to developing countries are estimated to have reached $351 billion in 2011, up 8 percent over 2010. For the first time since the global financial crisis, remittance flows to all six developing regions rose in 2011. Growth of remittances in 2011 exceeded our earlier expectations in four regions, especially in Europe and Central Asia (due to higher outward flows from Russia that benefited from high oil prices) and Sub-Saharan Africa (due to strong south-south flows and weaker currencies in some countries that attracted larger remittances). By contrast, growth in remittance flows to Latin America and Caribbean was lower than previously expected, due to continuing weakness in the U.S. economy and Spain. Remittance costs have fallen steadily from 8.8 percent in 2008 to 7.3 percent in the third quarter of 2011. However, remittance costs continue to remain high, especially in Africa and in small nations where remittances provide a life line to the poor.